2020
DOI: 10.37932/ja.v9i2.141
|View full text |Cite
|
Sign up to set email alerts
|

Pentingnya Pemahaman Akuntansi Sederhana Sebagai Solusi Untuk Menyusun Laporan Keuangan

Abstract: Financial reports serve as a tool for analyzing financial performance that can provide information about business finances so that they can be used as a basis for making decisions. The object of this research is UD Rian Arianto Farm, which is engaged in the farming and trade of native chickens in Bogor. The purpose of this research is to provide knowledge to Partners about the importance of compiling financial reports to carry out a business activity either manually or computerized which can make it easier for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
0
0
1
Order By: Relevance
“…There is still a stigma among micro, small, and medium-sized enterprise (MSME) actors that bookkeeping is difficult and intricate, so they avoid documenting business transactions. [15] This is in line with research conducted by Nanang Shonhadji, Laely Aghe A., and Djuwito with the research title "Application of Compilation of Financial Statements in Small and Medium Enterprises Based on Sak Emkm in Surabaya," whose research results are a lack of accounting knowledge [16] will affect the existing recording system in a business. [17] The results of the research according to Ni Komang Ismadewi, Nyoman Trisna Herawati, Anantawikrama Tungga Atmaja with the title "Preparation of Financial Statements in Accordance with Financial Accounting Standards for Micro, Small, and Middle School (SAK EMKM) in Boiler Chicken Livestock Business (Case Study on Business I Wayan Sudiarsa, Pajahan Village, Pupuan District, Tabanan Regency)" concluded that based on the results of interviews, it was stated that the format of the financial reports was created in a simplistic manner because they were unaware of the proper format.…”
Section: Program Implementation Stagesupporting
confidence: 73%
“…There is still a stigma among micro, small, and medium-sized enterprise (MSME) actors that bookkeeping is difficult and intricate, so they avoid documenting business transactions. [15] This is in line with research conducted by Nanang Shonhadji, Laely Aghe A., and Djuwito with the research title "Application of Compilation of Financial Statements in Small and Medium Enterprises Based on Sak Emkm in Surabaya," whose research results are a lack of accounting knowledge [16] will affect the existing recording system in a business. [17] The results of the research according to Ni Komang Ismadewi, Nyoman Trisna Herawati, Anantawikrama Tungga Atmaja with the title "Preparation of Financial Statements in Accordance with Financial Accounting Standards for Micro, Small, and Middle School (SAK EMKM) in Boiler Chicken Livestock Business (Case Study on Business I Wayan Sudiarsa, Pajahan Village, Pupuan District, Tabanan Regency)" concluded that based on the results of interviews, it was stated that the format of the financial reports was created in a simplistic manner because they were unaware of the proper format.…”
Section: Program Implementation Stagesupporting
confidence: 73%
“…Pemahaman akuntansi yang baik yang dilakukan oleh staf keuangan akan mengurangi kesalahan dalam pembuatan laporan keuangan sehingga output laporan keuangan yang disajikan berkualitas, dapat berguna bagi stakeholdernya, dan berfungsi sebagai pengambil keputusan kinerja LPD berikutnya.Apabila tingkat pemahaman akuntansi semakin meningkat maka akan dapat meningkatkan kualitas laporan keuangan LPD tersebut. Penelitian ini sejalan dengan penelitian Jha (2019) ; Riyadi (2020) ; dan Yanti & Nurhidayah (2020).…”
Section: Pengaruh Tingkat Pemahaman Akuntansi Terhadap Kualitas Pelaporan Keuangan Pada Lpd DI Kota Denpasarunclassified